Oral lichen planus in a young patient: a case report with nine-year follow-up - Moraes, Gustavo Simão; Huller, Daniela; Huk, Valéria Kruchelski; Kiratcz, Fagner; Urban, Vanessa Migliorini; Campagnoli, Eduardo Bauml (ABCS Health Sciences, 2023)
Introduction: Oral lichen planus is an inflammatory condition that affects the stratified squamous epithelium of the oral mucosa. It occurs more frequently in female patients and it is rarely observed in children, adolescents, or young adults. This study aims to report a case of oral lichen planus in a young patient with a nine-year follow-up. Case report: A 19-year-old man reported to the Dentistry Department with a complaint of an asymptomatic white lesion on the dorsum and left lateral border of his tongue, which had appeared a few weeks before. Two weeks later, a second lesion, very similar to the previous one, appeared on the central region of his tongue. An incisional biopsy was performed. The histological slides were stained with hematoxylin-eosin and the expression of interleukin-1beta (IL-1β) and tumor necrosis factor-alpha (TNF-α) was assessed by immunohistochemistry. No pharmacological treatment was prescribed. The clinical and histopathological findings were suggestive of oral lichen planus. The IL-1β/TNF-α expression was low. There was a spontaneous regression of the lesions after approximately one year. The nine-year follow-up showed no signs of recurrence. Conclusion: This case presents atypical features such as the age of the patient and the spontaneous remission of the lesions.